Neural signatures of dynamic emotion constructs in the human brain. (August 2020) - Grootswagers, Tijl; Kennedy, Briana L.; Most, Steven B.; Carlson, Thomas A.
Abstract: How is emotion represented in the brain: is it categorical or along dimensions? In the present study, we applied multivariate pattern analysis (MVPA) to magnetoencephalography (MEG) to study the brain's temporally unfolding representations of different emotion constructs. First, participants rated 525 images on the dimensions of valence and arousal and by intensity of discrete emotion categories (happiness, sadness, fear, disgust, and sadness). Thirteen new participants then viewed subsets of these images within an MEG scanner. We used Representational Similarity Analysis (RSA) to compare behavioral ratings to the unfolding neural representation of the stimuli in the brain. Ratings of valence and arousal explained significant proportions of the MEG data, even after corrections for low-level image properties. Additionally, behavioral ratings of the discrete emotions fear, disgust, and happiness significantly predicted early neural representations, whereas rating models of anger and sadness did not. Different emotion constructs also showed unique temporal signatures. Fear and disgust – both highly arousing and negative – were rapidly discriminated by the brain, but disgust was represented for an extended period of time relative to fear. Overall, our findings suggest that 1) dimensions of valence and arousal are quickly represented by the brain, as are some discrete emotions, and 2) different emotion constructs exhibit unique temporal dynamics. We discuss implications of these findings for theoretical understanding of emotion and for the interplay of discrete and dimensional aspects of emotional experience. Highlights: MEG was recorded while participants performed a 1-back task with emotional images. Temporal neural signatures of emotional constructs were analyzed using MVPA. Valence, arousal and discrete emotions were differentiable from the MEG response. Findings suggest several emotional constructs are represented early and distinctly. Different time courses may represent the way emotions are constructed.